Comparing Personal Image Collections with PICTuReVis - van der Corput, Paul; van Wijk, Jarke J. (Computer graphics forum, 2017)
Digital image collections contain a wealth of information, which for instance can be used to trace illegal activities and investigate criminal networks. We present a method that enables analysts to reveal relations among people, based on the patterns in their collections. Similar temporal and spatial patterns can be found using a parameterized algorithm, visualization is used to choose the right parameters and to inspect the patterns found. The visualization shows relations between image properties: the person it belongs to, the concepts in the image, its time stamp and location. We demonstrate the method with image collections of 10, 000 people containing 460, 000 images in total.